O perfil socioeconômico de mães de pessoas com deficiência - Figueiredo, Jander Phillipe Diniz (Brasil, 2022)
The objective of the research was to identify the socioeconomic profile of mothers of people with disabilities. Forty mothers of children with cerebral palsy, intellectual disability, autism, schizophrenia, down syndrome, multiple disability, traumatic brain injury, visual impairment, niemann-pick and myelo participated in the research. Data collection took place at the Federal University of Amazonas, through the Motor Activities Program for the Disabled (PROAMDE), with the signing of the Informed Consent Term (ICF). A questionnaire was used as a collection instrument. The instruments used for data collection were: questionnaires with research-oriented questions. As for the results, it was identified that mothers, having to take care of their children, end up leaving their desires aside, negatively correlating with the socioeconomic level. It is concluded that the study identified important correlations, especially with regard to groups of mothers in vulnerability, in addition, it was found that many live in difficult situations with their children, requiring the constant elaboration of daily activities and strategies for their better development.